NUTRITIONAL STRATEGIES FOR LAYING HENS TO ADDRESS ENVIRONMENTAL CHALLENGES BY REDUCING THE NITROGEN EXCRETION - Vlaicu, Petru Alexandru; Untea, Arabela Elena; Panaite, Tatiana Dumitra; Cornescu, Gabriela Maria; Saracila, Mihaela; Varzaru, Iulia; Oancea, Alexandra Gabriela (Food and Feed Research, 2024)
This research aimed to assess the impact of incorporating Castanea sativa powder into laying hens diets, examining reduced crude protein levels and their effects on production performance, health status, nutrients and mineral digestibility and environmental pollution by nitrogen (N) excretion and absorption. For that, a 6-week trial was developed, with 90 Lohmann Brown laying hens aged 51 weeks, raised in digestibility cages, divided into three groups with 30 hens each. The diets were composed as follows: a control group fed with 17.50% crude protein (CON), an experimental group with a reduced protein level of 15.50% (RPL), and a similar reduced protein group supplemented with 0.5% Castanea sativa powder (RPCs) as tannin supplement. The limiting amino acids (lysine, methionine, and threonine) were supplemented to maintain constant equal amino acid concentrations in all experimental diets. Throughout the trial, the laying intensity was higher in the RPCs group (94.12%), followed by RLP (93.65%) and CON (91.11%). However, the CON hens yielded heavier eggs compared to RPL and RPCs groups. Average daily feed intake and feed conversion ratio showed no significant differences among the groups. Health assessments from blood samples taken at the end of the trial showed a significant effect in monocytes, and uric acid among the groups with tendencies for leucocytes, lymphocytes, heterophiles. Notably, excreted nitrogen levels were significantly reduced (up to 30%) in experimental groups compared with the CON group, showing a promising way of reducing N pollution. On the other hand, the apparent absorption of protein was higher in the groups with lower levels of protein in the diet (RPL and RPCs) compared with CON group.
Keywords: Castanea sativa, health status, performances, poultry, protein levels, nitrogen balance.